Generating Equity-Oriented Partnerships: A Framework for Reflection and Practice - Leah Anne Teeters; A. Susan Jurow (The University of Alabama, 2022)
Research that links action across multiple scales of practice is particularly relevant for organizing consequential social change. The aim of this article is to present an evaluation framework to support community-based researchers in generating methods of engagement that can expand opportunities for non-dominant community members across scales of practice. Drawing on a five-year community-engaged research project, this article presents a framework outlining five dimensions of a community-engaged research trajectory: (1) establishing partnerships; (2) developing trust; (3) working with diverse linguistic practices; (4) planning for different forms of action; and (5) outcomes and dissemination. This is developed as a formative evaluation tool intended to be used throughout the research collaboration to inform the iterative process of learning collaborations and design work.